The Effect of Concussion History on Lower Extremity Injury Risk in College Athletes: A Systematic Review and Meta-Analysis - Vanessa Ramirez; Ryan McCann; Eric Schussler; Jessica Martinez (International Journal of Sports Physical Therapy)
# Introduction